Color in the Corners: ITO‐Free White OLEDs with Angular Color Stability. (13th May 2013) - Gaynor, Whitney; Hofmann, Simone; Christoforo, M. Greyson; Sachse, Christoph; Mehra, Saahil; Salleo, Alberto; McGehee, Michael D.; Gather, Malte C.; Lüssem, Björn; Müller‐Meskamp, Lars; Peumans, Peter; Leo, Karl
<x xml:space="preserve">Abstract</x> High‐efficiency white OLEDs fabricated on silver nanowire‐based composite transparent electrodes show almost perfectly Lambertian emission and superior angular color stability, imparted by electrode light scattering. The OLED efficiencies are comparable to those fabricated using indium tin oxide. The transparent electrodes are fully solution‐processable, thin‐film compatible, and have a figure of merit suitable for large‐area devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>